Juridical Analysis and Implementation of Ijarah Muntahiya Bit Tamlik (IMBT) Contracts in Sharia Banking: An Overview of the Elements, Anatomy of the Contract, and Legal Basis - Sinthya Wahyu Eka Pratiwi; Silviatus Sholihah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The development of Islamic banking encourages innovative financing products that arein accordance with sharia principles, one of which is Ijarah Muntahiya Bit Tamlik(IMBT). This contract combines a leasing transaction with a promise of transfer ofownership at the end of the contract term. This study aims to analyze the juridicalaspects, contractual elements, and anatomy of IMBT in Indonesian Islamic bankingpractices. This research uses normative legal research using legal and conceptualapproaches. The results of the study show that IMBT has an adequate legal foundationboth in sharia law and positive law; However, practical implementation still facespotential issues related to contract separation, WA'd clauses, and maintenanceresponsibilities. Therefore, stronger contract standardization and sharia complianceare needed to ensure IMBT practices remain consistent with prudential and shariaprinciples.Keywords: IMBT, ijarah, Islamic banking, contract, Islamic law